Rectal leiomyosarcoma - Viola Núñez, Humberto; Praderi, Luis; Reissenweber, Nelson (Cirugía del Uruguay, 1995)
A case of leiomyosarcoma of the rectum is presented and bibliography on the subject is analysed. They are extreme/y rare tumors whose diagnosis is made by means of rectal examination and rectosigmoidoscopy. Treatment consists of abdominoperineal amputation and adjuvant chemotherapy. They have a low survival rate at 5 and 1 O years.